Pengujian Abnormal Return Saham Sebelum dan Sesudah Peluncuran Indeks MNC36 (Studi Kasus Perusahaan yang Terdaftar pada Lampiran Surat Pengumuman Indeks MNC36 No.Peng-00529/BEI.PSH/08-2013) - Barokah, Siti; Witiastuti, Rini Setyo (Universitas Negeri Semarang, 2016)
The purpose of this research is to explain the reaction showed by the difference of abnormal return before and after MNC36 announcement. This study using event study, by observation of the abnormal return during the event period, ie 15 days before to 15 days after the MNC36 announcements. This research used the event study, which was conducted observation of abnormal return during the event period, i.e. before 15 days up to 15 days after the MNC36 announcements. The population in this research are all companies share listed on the MNC36 in 2013. The sampling technique was conducted with a purposive sampling method and obtained a sample of 33. The data analyzes were used One Sample Kolmogorov-Smirnov test for data normality test, and hypothesis testing used One Sample T-test and Paired Samples T-Test for data which are normally distributed. The result of One Sample T-test and Paired Sample T-test showed that there is no abnormal return in the period before and after the launch of the index MNC36. The suggestions for futher researchers can use other variables to describe reactions in the MNC36 announcement such as return and trading volume activity so it can be known the difference for comparative result.